Changes in positive and negative affect as predictors of change in felt age: Results from the Health and Retirement Study. Issue 6 (2nd November 2017) - Palgi, Yuval; Ayalon, Liat; Avidor, Sharon; Bodner, Ehud
Abstract: The present study aimed to examine how changes in positive and negative affect and their interaction predict changes in felt age in a longitudinal design of two waves drawn from the Health and Retirement Study (HRS). Participants ( n  = 4174) at an average age of 67.97 completed the 2008 and 2012 left behind questionnaire of the HRS. Our results showed that an increase in positive affect and a decrease in negative affect from Wave 1 to Wave 2 predicted an accelerated decrease in felt age. There was an interaction effect showing that for those with an increase in negative affect, a higher change in positive affect predicted reduced odds for accelerated increase in felt age. To conclude, improving favorable change in the combination between positive and negative affect might in turn relate to the individual's self-perceptions of aging, in the second half of life.